Observations on "Renegade View of What We Do" - Joseph J. Marks (Journal of Applied Communications, 1979)
Care and Feeding of The Ego Ouch! Don Wells' shots hit darn close to home. It worries me that I had to read some of these bloopers about four times before catching the mistakes.